Vitamin K Content of Raw and Cooked U.S. Beef Variety Meat Items (FS14-03-19). (13th June 2019) - Schneider, Kaylie; Kesterson, Hannah; Woerner, Dale; Ellis, Jessie; Haytowitz, David; Booth, Sarah; Fu, Xueyan; Roseland, Janet
Abstract: Objectives: Vitamin K is an essential nutrient that has been implicated in cardiovascular disease and other chronic diseases. There are two forms of vitamin K in nature. Phylloquinone (PK) is plant-based and has been well-quantified in the U.S. diet. Menaquinones (MK) are found in animal products and fermented food. However, the MK contents of food have not been well characterized. The objectives of this study were to: 1) quantify the different forms of MK (MK4 through MK13) in the beef variety meat items; and 2) determine if cooking has an effect on vitamin K content of beef variety meat items. Methods: Raw beef heart, liver, kidney, tongue, honeycomb tripe, oxtail, bone marrow, beef rocky mountain oysters (RMO), fat composite samples and blood (total samples n = 31) were obtained from processing facilities in the U.S., to provide national representation of retail-ready beef variety meat items. All raw beef samples were cooked, and final internal temperature was 80 °C. PK and the MKs in raw and cooked beef variety meat items were quantified using mass spectrometry technology. Wilcoxon Rank Signed test was used to compare PK and MK contents of raw and cooked samples. Differences were considered statistically significant at P  < 0.05. Results: The highest concentration of any form was PK in bone marrow at 152 ± 11.9 ng/g. The fat composite samples contained between 20.9 ng/g to 63.0 ng/g of PK. Modest amounts of PK were found in liver, RMO and tripe. MKs were present in all samples analyzed with MK4, MK10, MK12 and MK13 present in the largest amount in the analyzed samples. MK4 concentrations in bone marrow and fat composite samples were 341 ± 116 and 374 ± 101 ng/g, respectively. Liver contained appreciable amounts of longer-chain MKs, primarily in the forms of MK11, MK12 and MK13, which together accounted for 95% of total vitamin K in liver. There were no significant differences in total vitamin K content between cooked and uncooked beef variety. Conclusions: To the best of our knowledge, this is the first report of MK contents of U.S. beef variety meat items. The vitamin K content of beef items were not influenced by cooking (heating). Funding Sources: Funded by the Beef Checkoff and supported by the USDA, Agricultural Research Service under Cooperative Agreement.